The Ideal Age of Marriage in Indonesian Family Law: An Integrative Analysis of Islamic and Positive Law - Afrinald Rizhan; Akbarizan Akbarizan; Zailani Zailani (Hukum Keluarga Islam IAIN LANGSA, 2025)
The determination of the ideal age of marriage remains a critical issue in Indonesia, where child marriage persists despite the enactment of Law No. 16 of 2019, which raised the minimum marriage age to nineteen. This article aims to formulate an integrative model that combines procedural safeguards under positive law with the substantive readiness criteria of rusyd in Islamic jurisprudence. The study employs a normative-juridical method with comparative analysis, drawing on primary sources (the Quran, classical fiqh, and statutory law) and secondary empirical data from BPS, UNICEF, and religious court decisions. The comparative framework is structured across three dimensions: (1) legal objectives (maqasid al-shariah and child protection norms), (2) substantive indicators of marital readiness (psychological, financial, and emotional maturity), and (3) procedural instruments (statutory age thresholds and judicial dispensations). The findings reveal that while positive law provides procedural certainty through age limits, its effectiveness is weakened by frequent dispensations that rarely assess readiness. Conversely, Islamic law emphasizes rusyd as a holistic benchmark but lacks enforceable procedural mechanisms. This study proposes a dual-layered model in which statutory age serves as a procedural safeguard, while readiness assessments operationalize rusyd as substantive criteria. The originality of this research lies in the proposal of a readiness assessment instrument for religious courts, designed to standardize judicial discretion in marriage dispensation cases. By integrating doctrinal analysis with socio-legal evidence, the study not only advances family law scholarship but also offers concrete policy implications. In practice, the readiness assessment can serve as a tool for judges to evaluate applicants’ intellectual, emotional, and socio-economic maturity, thereby reducing the incidence of early marriages approved through dispensations. This approach strengthens family resilience, aligns judicial practice with the objectives of maqasid al-shariah, and ensures that legal reforms are translated into measurable improvements in child protection and community well-being.